THE EFFECTIVENESS OF SELF QUESTIONING STRATEGY IN TEACHING READING NARRATIVE TEXT - Elisah, .; Sada, Clary; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research is to find out how effective Self Questioning Strategy in teaching reading narrative text to the tenth grade students of SMA Negeri 5 Pontianak in Academic Year 2014/2015. This research was a pre-experimental study. This research involves pre-test and post-test to measure the effectiveness of the treatment.The technique of collecting data is measurement technique. The form of the instruments are multiple choices. The instruments to collect the data are pre test and post test. Pre-test was administered before the treatment is given. Meanwhile, post-test is administered after the treatment is given. The different mean score of pre-test and post-test is respectively 41.14 and 55.71. The t-test is higher with 3.09 is higher than t-table with 2.032 for the degree of freedom of 34 and the Effect Size is 0.53 and categorized moderate effect.The result shows that the effectiveness of self questioning strategy in teaching reading narrative text is moderate. Key words: Self Questioning Strategy, reading comprehension Abstrak: Tujuan dari riset ini adalah untuk mengetahui seberapa efektifnya Strategi Self Questioning dalam mengajarkan teks naratif kepada siswa SMA Negeri 5 Pontianak pada tahun ajaran 2014/2015. Riset ini menggunakan pre test dan post test untuk mengukur keefektifan treatment tersebut. Tehnik pengumpulan data dalam riset ini adalah measurement tehnique. Bentuk test yang digunakan adalah pilihan ganda. Test yang digunakan dalam pengumpulan data adalah pre test dan post test. Pre test dilakukan sebelum treatment diberikan. Sementara itu, post test dilakukan setelah treatment diberikan. Perbedaan nilai mean pada pre test dan post test masing-masing adalah 41.14 dan 55.71. Nilai t-test yang didapatkan adalah 3.09 yang mana lebih tinggi dari nilai t-table yaitu 2.032 untuk degree of freedom 34 dan nilai Â Effect Size-nya yaitu 0.53 dan dikategorikan cukup berpengaruh. Hasil dari riset ini menunjukan bahwa keefektifan strategi self questioning dalam mengajar teks naratif adalah cukup berpengaruh. Kata Kunci: Self Questioning Strategy, reading comprehension